Amyloid Precursor Protein Processing in Alzheimer’s Disease - BHADBHADE, Adwait; CHENG, Davis Weizhong (Iranian Journal of Child Neurology, 2012)
How to Cite this Article: Bhadbhade A, Cheng DW. Amyloid Precursor Protein Processing in Alzheimer’s Disease. Iranian Journal of Child Neurology2012;6(1):1-5. Alzheimer’s disease (AD) is a progressive neurodegenerative disorder and a leading cause of dementia. The AD is characterized by presence of intraneuronal tangles and extracellular plaques in the brain. The plaques are composed of dense and mostly insoluble deposits of amyloid beta peptide (Aβ), formed by sequential cleavage of the Amyloid Precursor Protein (APP), by two pathways amyloidogenic and non-amyloidogenic. Tangles are composed of paired helical fragments, which aggregate to form, microtubular protein tau. Although Aβ plaques are established to be the cause of the disease, there exist genetic factors and other pathological identifications in addition to these which are an integral part of the disease. This article gives an overview into the mechanism of APP action, genetic factors and other pathological identifications contributing to Alzheimer’s disease formation. References Brookmeyer R, Gray S, Kawas C. Projections of Alzheimer’s disease in the United States and the public health impact of delaying disease onset. American Journal of Public Health 1998;88(9):1337. Hebert LE, Scherr PA, Bienias JL, Bennett DA, Evans DA. Alzheimer disease in the US population. Arch Neurol 2003;60(8):1119-22. Möller HJ, Graeber M. The case described by Alois Alzheimer in 1911. European Archives of Psychiatry and Clinical Neuroscience 1998:248(3):111-122. Selkoe D J. (2002). Deciphering the genesis and fate of amyloid beta-protein yields novel therapies for Alzheimer disease. J Clinic Investigat 2002;110(10): 1375-82. Wolfe MS. Tau mutations in neurodegenerative diseases. J Biolog Chem 2009;284(10):6021. Selkoe DJ. Alzheimer’s disease: genes, proteins, and therapy. Physiological reviews 2001;81(2):741. Selkoe DJ. The cell biology of [beta]-amyloid precursor protein and presenilin in Alzheimer’s disease. Trends in Cell Biology 1998;8(11):447-453. Thinakaran G, Koo EH. Amyloid precursor protein trafficking, processing, and function. Journal of Biological Chemistry 2008;283(44):29615. Zhang YW, Thompson R, Zhang H, Xu H. APP processing in Alzheimer’s disease. Mol Brain 2011;4:3. doi: 1756- 6606-4-3 [pii] 10.1186/1756-6606-4-3. Nunan J, Small DH. Regulation of APP cleavage by α-,β- and γ-secretases. J Biolog Chem 2000:483(1):6-10. Pearson HA, Peers C. Physiological roles for amyloid peptides. J Physiology 2006;575(1):5-10. Wang Y, Ha Y. The X-ray structure of an antiparallel dimer of the human amyloid precursor protein E2 domain. Molecular Cell 2004;15(3):343-353. Quitschke WW, Goldgaber D. The amyloid b-protein precursor promoter. Journal Biolog Chem 1992;267(24):17362-17368. Vostrov AA, Taheny MJ, Izkhakov N, Quitschke WW. A nuclear factor-binding domain in the 5’-untranslated region of the amyloid precursor protein promoter: implications for the regulation of gene expression. BMC Research Notes 2010;3:4. Ghosala K,Vogta D, Lianga M, Shenb Y, Lamba BT, Sanjay W, Pimplikara SW. Alzheimer’s disease-like pathological features in transgenic mice expressing the APP intracellular domain. Proceedings of National Academy of Sciences 2009;106(43):18367-77.